Study on the technological and economic viability of introducing energy storage systems with solar photovoltaic panels - Barros, Luis A. M. (2019)
Solar photovoltaic represent one of the most promising technologies for generating electrical energy from renewable sources. In fact, as a result of the technological advances in the field of microelectronics and power electronics, photovoltaic systems have reached historic lows in terms of costs, surpassing the other types of renewable energy sources. The potential of the solar photovoltaic systems is enormous, being capable of meeting the energy needs of today, without compromising future needs, and allowing a sustainable development. With this in mind, several incentives and, consequently, legislations have been implemented around the world. In the Portuguese case, depending on the type of contract, for photovoltaic solar installations with value of power up to 1500 Wp the production surplus is injected into the power grid without any financial compensation. Considering the high investment, particularly regarding the photovoltaic panels, the support structure and the power electronics converters, it could be interesting to implement a system capable of storing the surplus energy for later use by the owner of the photovoltaic installation. This paper presents a study on the viability of energy storage systems in photovoltaic installations up to 1500 Wp. For this study, different consumer profiles, types of installations and geographic locations were considered, in order to perceive the technological and economic viability of this solution.